(untitled) (Damascus University Journal of agriculture sciences, 2021)
Abstract The investigation was carried out during 2017 - 2018 at the laboratories of Plant Protection Dept., Faculty of Agriculture, Damascus University, to determine the constituents of the methanol extract isolated from leaves of Datura stramonium L, grown in Damascus, Syria, A total of 9 components were identified in methanol extract of D. stramonium seeds by GC-MS. The methanol extract is rich with fatty acid , where found 26.43% from the total contents of extract. Furthermore, Alkolide components, scopolamine (21.43%) and atropine (5.46%). Also, methanol extract of D. stramonium seeds exhibited antifungal activity using the poison media method against Aspergillus niger, A. flavus, Penicillium expansum, Fusarium solani and F. oxysporum f.sp. lycopersici. Methanol extract of D. stramonium was superior antifungal activity to A. flavus and F.solani, where, the ED50 were, 185 and 512 ppm respectively. and lowest effect on the P. expansum fungus. Therefore we recommended to use the Methanol extract of D. stramonium as environment friendly fungicides.